Recommending similar users using moving patterns in mobile social networks. (July 2019) - Bok, Kyoungsoo; Lee, Chunghui; Yoo, Jaesoo
Abstract: Recently, studies on recommendations appropriate to user preferences have been conducted through the trajectory analyses of users. In this paper, we propose a similar user recommendation scheme considering the attribute information of points of interest (POIs) and user's moving patterns. The proposed scheme broadly consists of a part that filters out other users who have different preferences by calculating preferences using the attribute information of users and a part that finds a moving trajectory that is close to that of users by using a pattern-matching. To evaluate the performance of the proposed scheme, the similarity of the POI trajectories of other users recommended as similar users and that of a user was verified.